2018
DOI: 10.1186/s13068-018-1033-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for cell wall composition traits measured using near-infrared spectroscopy in the model C4 perennial grass Panicum hallii

Abstract: BackgroundBiofuels derived from lignocellulosic plant material are an important component of current renewable energy strategies. Improvement efforts in biofuel feedstock crops have been primarily focused on increasing biomass yield with less consideration for tissue quality or composition. Four primary components found in the plant cell wall contribute to the overall quality of plant tissue and conversion characteristics, cellulose and hemicellulose polysaccharides are the primary targets for fuel conversion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Group II was comprised entirely of species of the genus Oryza and had a bootstrap value of 100%, which indicates the extremely high reliability of the group. Except for the C3 grass Dichanthelium oligosanthes (OEL14197.1) ( Studer et al, 2016 ), all other species in Group III were C4 plants, which included three species of the genus Panicum ( P. virgatum ( Flint et al, 2019 ), P. hallii ( Milano et al, 2018 ), and P. miliaceum ( Son & Sugiyama, 1992 )) and two species of the genus Setaria ( S. italica ( Heimann et al, 2013 ) and S. viridis ( Brutnell et al, 2010 )). The group also consisted of two genes from Z. mays ( BD1 and BD1B ), one gene from S. bicolor ( Paterson et al, 2009 ; Tazoe et al, 2016 ), and two genes from Saccharum spontaneum ( Zhang et al, 2018 ).…”
Section: Results and Analysismentioning
confidence: 99%
“…Group II was comprised entirely of species of the genus Oryza and had a bootstrap value of 100%, which indicates the extremely high reliability of the group. Except for the C3 grass Dichanthelium oligosanthes (OEL14197.1) ( Studer et al, 2016 ), all other species in Group III were C4 plants, which included three species of the genus Panicum ( P. virgatum ( Flint et al, 2019 ), P. hallii ( Milano et al, 2018 ), and P. miliaceum ( Son & Sugiyama, 1992 )) and two species of the genus Setaria ( S. italica ( Heimann et al, 2013 ) and S. viridis ( Brutnell et al, 2010 )). The group also consisted of two genes from Z. mays ( BD1 and BD1B ), one gene from S. bicolor ( Paterson et al, 2009 ; Tazoe et al, 2016 ), and two genes from Saccharum spontaneum ( Zhang et al, 2018 ).…”
Section: Results and Analysismentioning
confidence: 99%
“…Therefore, our results can contribute to the search for important genomic regions in other forage species. In contrast, in forage grasses of temperate climates, such as Panicum hallii (Milano et al, 2018) and Lolium perenne (Cogan et al, 2005), QTLs for nutritional and agronomic traits have been identified, even by using only single-dose markers.…”
Section: Qtls For Agronomic and Nutritional Traitsmentioning
confidence: 99%
“…Near-infrared spectroscopy (NIRS) paired with multivariate analysis offers a fast and non-invasive method to determine these traits [ 23 ]. Importantly, NIRS models have been established for determining major wall polymers of rice [ 24 ], bamboo [ 25 ], Miscanthus [ 26 ], and sweet sorghum [ 27 ], but it is rarely applied to assist QTL mapping for lignocellulose recalcitrant traits [ 28 ]. Thereby, it remains interesting to combine NIRS modeling with QTL mapping for investigating minor monosaccharide roles in wall network construction and lignocellulose enzymatic saccharification.…”
Section: Introductionmentioning
confidence: 99%